PARENTERAL PARAQUAT POISONING : A FATAL CASE REPORT AND PATHOLOGICAL FINDINGS REVIEW - Hoonvijit, Udomsak (ศรีนครินทร์เวชสาร, 2013)
ABSTRACT Paraquat is a popular and widely used herbicide in many countries all over the world. All cases of paraquat poisoning in Thailand had been reported to induce via oral, inhalation or percutaneous routes. Here we report the first case of parenteral paraquat poisoning of a 17 year old male with a problem of parenteral amphetamine addict who committed suicide by paraquat via intravenous administration. His clinical and laboratory investigations including autopsy were performed. Paraquat and opiated compound were detected in his urine and amphetamine was detected in liver. The death ensured from progressive diffuse cellular intraalveolar and intravascular fibrosis (paraquat lung) with complication of pneumonia and septicemia at 11th day after administration (5 days after hospital admission)